2012
DOI: 10.1111/j.1439-0426.2011.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

The use of otolith shape and morphometry for identification and size-estimation of five wrasse species in predator-prey studies

Abstract: Sagittal otoliths of five wrasse species, Coris julis, Symphodus tinca, Symphodus cinereus, Symphodus ocellatus and Symphodus rostratus from the eastern Adriatic were compared using descriptive morphological characters (types of anterior and posterior otolith regions and otolith margins) and shape indices (formfactor, roundness, circularity, rectangularity and elipticity). All shape indices except the formfactor were used to build the discriminant function, with circularity and roundness being the main variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 25 publications
5
34
0
1
Order By: Relevance
“…Otolith biometrybody length relationships were defined using linear models for various fish species (Echeverria, 1987;Şahin and Güneş, 1998;Harvey et al, 2000;Şen et al, 2001;Morley and Belchier, 2002;Bostancı, 2009;Battaglia et al, 2010;Zorica et al, 2010;Jawad et al, 2011;Bostancı et al, 2012;Basusta et al, 2013;Felix et al, 2013). However, nonlinear models were used to generate the mentioned relationships for some fishes (Waessle et al, 2003;Kumar et al, 2012;Skeljo and Ferri, 2012). In this study, curvilinear and linear functions provided the best fit for 80% and 20% of all species, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Otolith biometrybody length relationships were defined using linear models for various fish species (Echeverria, 1987;Şahin and Güneş, 1998;Harvey et al, 2000;Şen et al, 2001;Morley and Belchier, 2002;Bostancı, 2009;Battaglia et al, 2010;Zorica et al, 2010;Jawad et al, 2011;Bostancı et al, 2012;Basusta et al, 2013;Felix et al, 2013). However, nonlinear models were used to generate the mentioned relationships for some fishes (Waessle et al, 2003;Kumar et al, 2012;Skeljo and Ferri, 2012). In this study, curvilinear and linear functions provided the best fit for 80% and 20% of all species, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Otolith length (the greatest distance between anterior and posterior otolith margin) and otolith width (the greatest distance from dorsal to ventral otolith margin for the asteriscus and from lateral to medial margin for the lapillus) were measured to the nearest 0.001 mm using Leica Application Suit Ver. 3.8 Imaging Software (Skeljo and Ferri, 2012). The right and left otoliths were considered separately.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, FL-WO relationship (r 2 = 0.651) is lower than FL-OL relationship (r 2 = 0.751) for Engraulis encrasicolus (Zorica et al, 2010). The similar results were shown for Coris julis (FL-OL (r 2 )= 92.7, FL-WO (r 2 )= 88.2), Symphodus tinca (FL-OL (r 2 )= 86.5, FL-WO (r 2 )= 80.6), Symphodus cinereus (FL-OL (r 2 )= 57.3, FL-WO (r 2 )= 52.4), Symphodus ocellatus (FL-OL(r 2 )= 51.6, FL-WO (r 2 )= 44.7) (Skeljo & Ferri, 2012). In addition, similar results for one of the Cyprinid fish Capoeta banarescui, which is a freshwater fish, were shown that the relationship between total length and otolith weight (r 2 =0.56) is lower than the other relationships between otolith length (r 2 = 0.88) and otolith width (r 2 = 0.83) (Keskin).…”
Section: Resultsmentioning
confidence: 99%
“…Penelitian hubungan antara morfometrik otolith dan ukuran ikan sangat berguna untuk mengestimasi ukuran riil individu ikan yang telah tercerna, baik panjang dan beratnya, sebagai pendukung dalam kajian hubungan pemangsa dan mangsa (predator and prey relationship) (Granadeiro & Silva, 2000;Skeljo & Ferri, 2012). Hubungan antara morfometrik otolith dan ukuran ikan dapat digunakan untuk penghitungan balik (back-calculation) ukuran ikan yang telah dimangsa/tercerna (Zan et al, 2015).…”
Section: Hubungan Morfometrik Otolith Dan Ukuran Ikan Lemuruunclassified